THE URGENCY OF IHSAN AND THINKING SYSTEMIC IN INCREASING MOTIVATION AND QUALITY OF EDUCATION - Azmi, Ulil; Rosadi, Kemas Imron; Zebua, Ali Marzuki (Teunuleh Publisher, 2022)
The implementation of ihsan in life is very urgent, this is because ihsan will bring happiness in birth and mind. Systemic thinking will encourage something to produce according to expectations. This behavior can be realized by activating all kinds of elements that exist in an institution. The existence of Ihsan will make a person careful in acting and cultivate self-confidence from within while invoking divine rida, so as to increase motivation and quality in an educational institution. Systemic thinking requires motivation from the inside (intrinsic) and from the outside (extrinsic) to realize the components present in the systemic thinking device. So, the implementation of the Ihsan concept is very urgent to be applied to educational institutions. This can be applied through systemic thinking. So that in the end, with the realization of the concept of ihsan, it will provide motivation to institutions in thinking systemically to improve the quality of education. The purpose of writing this article is to build a hypothesis of influence between variables to be used in future research. The results of this study are 1) The urgency of Ihsan affects motivation; 2) Systemic Thinking affects Motivation ; 3) The urgency of Ihsan affects the Quality of Education 4) Thinking System affects the Quality of Education and 5) Motivation affects the Quality of Education.